CaMKII‐dependent phosphorylation of GluK5 mediates plasticity of kainate receptors. (4th January 2013) - Carta, Mario; Opazo, Patrizio; Veran, Julien; Athané, Axel; Choquet, Daniel; Coussen, Françoise; Mulle, Christophe
Abstract : Calmodulin‐dependent kinase II (CaMKII) is key for long‐term potentiation of synaptic AMPA receptors. Whether CaMKII is involved in activity‐dependent plasticity of other ionotropic glutamate receptors is unknown. We show that repeated pairing of pre‐ and postsynaptic stimulation at hippocampal mossy fibre synapses induces long‐term depression of kainate receptor (KAR)‐mediated responses, which depends on Ca 2+ influx, activation of CaMKII, and on the GluK5 subunit of KARs. CaMKII phosphorylation of three residues in the C‐terminal domain of GluK5 subunit markedly increases lateral mobility of KARs, possibly by decreasing the binding of GluK5 to PSD‐95. CaMKII activation also promotes surface expression of KARs at extrasynaptic sites, but concomitantly decreases its synaptic content. Using a molecular replacement strategy, we demonstrate that the direct phosphorylation of GluK5 by CaMKII is necessary for KAR‐LTD. We propose that CaMKII‐dependent phosphorylation of GluK5 is responsible for synaptic depression by untrapping of KARs from the PSD and increased diffusion away from synaptic sites. Abstract : CamKII governs long‐term depression of kainate receptor (KAR) synaptic currents by phosphorylating the subunit GluK5, increasing its mobility and diffusion away from synaptic sites.